Associations between clinicopathological prognostic factors and pAkt, pMAPK and topoisomerase II expression in breast cancer - (:unkn) unknown (E-CENTURY PUBLISHING CORP, 2014)
This study aimed to examine the associations between mitogen activated protein kinase (MAPK), Akt, and topoisomerase II expression and other well established clinical and pathological prognostic factors in patients with breast cancer. A total of 42 women with breast cancer who underwent anthracycline based chemotherapy were included in this retrospective study. Immunohistochemical methods were utilized to examine the expression of phosphorylated MAPK (pMAPK), phosphorylated Akt (pAkt), HER-2/neu and topoisomerase II alpha (topo II alpha) in tissue blocks. Subsequently, the associations between pMAPK, pAkt, and topoisomerase IIa (topo IIa) expression characteristics and disease stage (T and N), tumor grade, estrogen/progesteron receptor status, and HER-2/neu expression were explored. Median age of the patients was 63 years (range, 37-82). There was a significant association between N stage and topoisomerase IIa expression (P = 0.021), with increasing rates of positivity in higher grades: N0, 22.7%; N1, 11.1%; N2, 42.9%; N3, 100%. In addition, topo IIa expression was higher in estrogen receptor-positive versus estrogen receptor-negative tumors (50% vs. 0%, P = 0.0004) and MAPK expression was more frequent among progesteron receptor-positive versus negative tumors (64.0 versus 20.0%, P = 0.027). Our results show that the tissue expression of topo II alpha and MAPK, which play a role in the intracellular signal pathways, is associated with certain established prognostic factors in breast cancer. Further studies examining survival rates and involving larger sample populations are warranted to better define the importance of the observed associations.
Keywords: Breast cancer; mitogen activated protein kinase (MAPK); Akt; topoisomerase II; human epidermal growth factor receptor-2/neu (HER-2/neu); ACTIVATED PROTEIN-KINASE; ANTHRACYCLINE-BASED THERAPY; HER-2 NEU ONCOGENE; ALPHA EXPRESSION; PREDICTIVE MARKERS; AMPLIFICATION; OVEREXPRESSION; CHEMOTHERAPY; SENSITIVITY; CARCINOMA